Cases in marketing financial services - Ennew, Christine; Watkins, Trevor; Wright, Mike (Oxford : Butterworth-Heinemann Ltd, 1993)
Written to complement "Marketing Financial Services" by the same authors, this casebook supplies specific practical applications for the principles, concepts and techniques developed in that text. T
Includes index
kjo 16/01/2019
Loans
Keywords: Financial services; Marketing; Financial industry; Financial services - marketing